Characteristics of the Surrounding Areas of BRT Stations in Jambi Province Based on Land-Use Diversity - Nindya Kusumaputri Suwarto; Bambang Hari Wibisono (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Jambi Provincial Government tries to overcome congestion by providing public transportation, Bus Rapid Transit (BRT) system, known as BRT Trans Siginjai Jambi. Public transportation Trans Siginjai Jambi has been operating for two years and has 11 BRT Stations. Placement of the transit node is one of the determinants of the role of bus stations in the surrounding area. The diversity of land-use and facilities close to the transit area can reduce travel time, so it is necessary to map the land-use that will determine the physical characteristics of the area around the BRT Station. This study discusses the characteristics of the area around the BRT Station using quantitative methods. Quantitative methods are used to determine the characteristics of BRT Station based on the variables of the proportion of land use in the area around the BRT Station. The land-use variable is obtained from the Transit-Oriented Development (TOD) theory. The study produced three characteristics of BRT Station, namely City Station, Neighborhood Station, and Special Activity Station.